In vitro propagation of two triploid hybrids of watermelon through adventitious shoot organogenesis and shoot tip culture - Shalaby, Tarek A.; Omran, Soliman A.; Baioumi, Yousry A. (Acta Biologica Szegediensis, 2008)
In vitro propagation protocol for two triploid hybrids of watermelon using cotyledon explants and shoot tips was achieved. Five benzyladenine (BA) concentrations were tested using cotyledon and shoot tip explants. Cotyledon explants and shoot tips from 6 and 15-20 days aseptically germinated were cultured on Murashige and Skoog medium (MS) containing test concentration of benzyladenine (2.22, 4.44, 10, 24.61 and 44.4 μM). Adventitious hoot organogenesis was initiated in all induction media and the differences among BA concentration were significant. MS medium containing 4.44, 10 and 24.61 μM BA showed the highest percentage of explants with shoots. The stimulation of axillary-bud development from excised shoot tips by a high cytokinin (BA) was observed. Axillary shoots were obtained from shoot tips of triploid watermelon and the multiplication rate ranged from 2 to 5.6 plants dependence on benzyladenine concentration and genotype. Obtained data showed that variation in regeneration rate was demonstrated. Shoots were excised and elongated in MS medium without hormones. The elongated shoots were rooted in MS medium containing 0.1 μM α-naphthalene acetic acid (NAA). Rooted plants were successfully acclimatized and gradually hardened-off to green-house conditions and subsequently established in soil with a survival rate of 80%.